Characterization of the Calcium Binding Protein Family in Zebrafish - Di Donato, Vincenzo (Public Library of Science, 2013)
Calcium Binding Proteins (CaBPs), part of the vast family of EF-Hand-domain containing proteins, modulate intracellular calcium levels. They thereby contribute to a broad spectrum of biological processes – amongst others cell migration, gene expression and neural activity. In this study we identified twelve members of this protein family in zebrafish including one gene (cabp4b) currently not present in the zebrafish genome assembly. To gain insight into their biological functions, we carried out a detailed analysis of the expression patterns of these genes during zebrafish late embryonic and early larval development. We detected specific transcription for most of them in different neuronal cell populations including the neuroretina, the inner ear and the notochord. Our data supports potential roles for CaBPs during neuronal development and function and provides a starting point for genetic studies to examine CaBPs' function in these tissues and organs.